New Perspectives on Plant Adenylyl Cyclases - Ruzvidzo, Oziniel; Gehring, Chris; Wong, Aloysius (Frontiers in Molecular Biosciences, 2019)
It is increasingly clear that plant genomes encode numerous complex multi-domain proteins that harbour functional adenylyl cyclase (AC) centres. These AC containing proteins have well-documented roles in development and responses to the environment. However, it is only for a few of these proteins that we are beginning to understand the intramolecular mechanisms that govern their cellular and biological functions as detailed characterizations are biochemically and structurally challenging given that these poorly conserved AC centres typically constitute only a small fraction (<10%) of complex plant proteins. Here, we offer fresh perspectives on their seemingly cryptic activities specifically showing evidence for the presence of multiple functional AC centres in a single protein and linking their catalytic strengths to the Mg2+/Mn2+-binding amino acids. We used a previously described computational approach to identify candidate multi-domain proteins from Arabidopsis thaliana that contain multiple AC centres and show, using an Arabidopsis leucine-rich repeat (LRR) containing protein (TAIR ID: At3g14460; AtLRRAC1) as example, biochemical evidence for multi-enzymatic activities. Importantly, all AC-containing fragments of this protein can complement the AC-deficient mutant cyaA in Escherichia coli while structural modelling coupled with molecular docking simulations, supports catalytic feasibility albeit to varying degrees as determined by the frequency of suitable substrate binding poses predicted for the AC sites. This statistic correlates well with the enzymatic assays which implied that the greatly reduced AC activities is due to the absence of the negatively charged [DE] amino acids previously assigned to cation-, in particular Mg2+/Mn2+-binding roles in ACs.